ALIAS (Albumin in Acute Ischemic Stroke) Trials: Analysis of the Combined Data From Parts 1 and 2 - Martin, Renee’ H.; Yeatts, Sharon D.; Hill, Michael D.; Moy, Claudia S.; Ginsberg, Myron D.; Palesch, Yuko Y. (Stroke (1970), 2016)
BACKGROUND AND PURPOSE—The ALIAS (Albumin in Acute Ischemic Stroke) part 1 and 2 trials evaluated whether 25% human serum albumin improves clinical outcomes after acute ischemic stroke above and beyond standard of care using similar protocols. The part 1 trial ended prematurely because of safety concerns, and the part 2 trial terminated early because of futility of finding a statistically significant effect of albumin over saline (control) administration. We combine the subject-level data of the part 1 and 2 trials to reevaluate the efficacy and safety outcomes with the larger sample size. METHODS—The combined data analyses closely follow those conducted in the part 2 trial. The primary outcome is the composite of the modified Rankin Scale and the National Institutes of Health Stroke Scale defined as a composite of modified Rankin Scale score 0 to 1 and National Institutes of Health Stroke Scale score 0 to 1 at 90 days from randomization. The unadjusted analyses use a simple Chi-square test, and those adjusting for baseline covariates use a generalized linear model with log link (to obtain relative risks). RESULTS—The participant characteristics at baseline were generally similar between the treatment groups and between the trials; however, thrombolysis use was greater in part 2 (84% versus 75%), and the upper age limit imposed in part 2 resulted in a younger sample (mean age in part 1 was 69 versus 64 in part 2). In the combined sample, the proportions of good outcome in the 2 treatment groups were identical (41%). Similar results were observed in all secondary efficacy outcomes. Pulmonary edema was a consistent safety concern, with a 6-fold increase in the albumin arm (13%) compared with saline (2%; relative risk =7.76, 95% confidence interval 3.87–15.57). CONCLUSIONS—Treatment with intravenous albumin 25% at 2 g/kg was not associated with improved outcome at 90 days and was associated with increased rates of intracerebral hemorrhage and pulmonary edema. CLINICAL TRIAL REGISTRATION—URLhttps://www.clinicaltrials.gov. Unique identifierNCT00235495.